2018
DOI: 10.2141/jpsa.0170022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phytosterols as Food Additives on Adrenal and Reproductive Endocrine Function during Sexual Maturation in Male Japanese Quail (<i>Coturnix coturnix japonica</i>)

Abstract: Varying amounts of phytosterols (PS) occur naturally in several foods of plant origin. PS, which are structurally and functionally similar to cholesterol, have been shown to reduce plasma total cholesterol (TC) and low-density lipoprotein-cholesterol (LDL-C) levels.Moreover, PS disrupts endocrine function in certain animals. In the present study, we investigated the effects of high doses of PS on adrenal and reproductive endocrine function during sexual maturation in Japanese male quails. Two experiments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…The long-term treatment of male rats with β-sitosterol resulted in decreased testicular weight and sperm concentration [ 28 ]. A more recent publication investigated the effects of phytosterols on the adrenal and reproductive functions of Japanese male quails [ 29 ]. Quail chronically fed with phytosterols significantly reduced testicular weight and testosterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term treatment of male rats with β-sitosterol resulted in decreased testicular weight and sperm concentration [ 28 ]. A more recent publication investigated the effects of phytosterols on the adrenal and reproductive functions of Japanese male quails [ 29 ]. Quail chronically fed with phytosterols significantly reduced testicular weight and testosterone levels.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of a study of goldfish (Carassius auratus) found that when exposed to alimentation with β-sitosterol, their blood levels of sex steroids decreased, accompanied by a reduction in the gonadal capacity to perform steroidogenesis (Maclatchy and Vanderkraak 1995). Qasimi et al (2018) conducted studies with quails (Coturnix japonica) in which they administered phytoestrogens. They concluded that the adrenal glands and gonads preferred cholesterol for performing steroidogenesis (Qasimi et al 2018).…”
Section: Phytosterolsmentioning
confidence: 99%
“…Qasimi et al (2018) conducted studies with quails (Coturnix japonica) in which they administered phytoestrogens. They concluded that the adrenal glands and gonads preferred cholesterol for performing steroidogenesis (Qasimi et al 2018). The testicles use LDL-C for this purpose, and when vegan or vegetarian diets rich in phytoestrogens were provided, this type of cholesterol decreased, as did steroidogenesis.…”
Section: Phytosterolsmentioning
confidence: 99%